Neutrophil-to-Lymphocyte Ratio and Comorbidities as Mortality Predictors for COVID-19 Patient at Dr. Moewardi Hospital Surakarta - Lawly Arrel Dionnie Greatalya; Dian Ariningrum; Lukman Aryoseto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
The COVID-19 pandemic has drawn global attention as its main health issue. The rapid transmission and the diverse degree of severity have caused complicacy in controlling the disease. A hematological lab test has been a standard procedure done during therapy. This study aimed to determine the relation of the hematological parameter as a COVID-19 mortality predictor. The cohort retrospective method was used for this study by observing the medical records of critically ill COVID-19 patients admitted at Dr. Moewardi Hospital, Surakarta, from May 2020 to June 2021. The observed variables in this study were age, gender, comorbidities, and hematological lab test towards the outcome. The results were then analyzed bivariate and multivariate with SPSS. Out of 161 data, 101 were found alive and 60 deceased. Bivariate analysis showed that age of 50-80 years (RR= 2.246; p=0.029), comorbidities (RR=2.891; p=0.008), leucocyte>9850/µl (RR=2.634; p=0.004), neutrophil percentage >84.25% (RR=4.808; p=0.000), lymphocyte percentage<22% (RR=0.065; p=0.008), and NLR>9.326 (RR=5.031; p=0.000) had a relationship with the outcome. Gender, hemoglobin level, and platelet did not significantly correlate with the patient's outcome. Multivariate analysis showed that a history of comorbidities (RR=2.9326; p=0.012) and NLR >9.326 (RR=5.073; p=0.000) were proven to be a good predictor for mortality of COVID-19 patients. This result can be advantageous for clinicians in predicting the mortality of COVID-19 patients.